First trimester exposure to anxiolytic and hypnotic drugs and the risks of major congenital anomalies: a United Kingdom population-based cohort study - Ban, Lu; West, Joe; Gibson, Jack E.; Fiaschi, Linda; Sokal, Rachel; Doyle, Pat; Hubbard, Richard; Smeeth, Liam; Tata, Laila J. (Public Library of Science, 2014)
BACKGROUND: Despite their widespread use the effects of taking benzodiazepines and non-benzodiazepine hypnotics during pregnancy on the risk of major congenital anomaly (MCA) are uncertain. The objectives were to estimate absolute and relative risks of MCAs in children exposed to specific anxiolytic and hypnotic drugs taken in the first trimester of pregnancy, compared with children of mothers with depression and/or anxiety but not treated with medication and children of mothers without diagnosed mental illness during pregnancy.